2015
DOI: 10.1016/j.jhydrol.2014.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Measuring well hydraulic connectivity in fractured bedrock using periodic slug tests

Abstract: 6Periodic hydraulic experiments were conducted in a five-spot well cluster completed in a single 7 bedding plane fracture. Tests were performed by using a winch-operated slug (submerged solid 8 cylinder) to create a periodic head disturbance in one well and observing the phase shift and 9 attenuation of the head response in the remaining wells. Transmissivity (T) and storativity (S) 10 were inverted independently from head response. Inverted T decreased and S increased with 11 oscillation period. Estimated S w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 23 publications
(12 reference statements)
7
56
1
Order By: Relevance
“…For example, Day-Lewis et al (2003 combined geophysical data and a conventional hydraulic test (a cross-hole test, not hydraulic tomography) as well as tracer tests to characterize the fracture-rock aquifer heterogeneity. Using the head responses induced by periodic slug tests, Guiltinan and Becker (2015) independently inverted the transmissivity and storativity in a sandstone bedrock containing a single, isolated subhorizontal fracture at the Altona Flat Rocks experimental site. They found that different oscillation periods lead to different estimates and periodic slug tests may be useful to establishing local scale spatial variability in hydraulic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Day-Lewis et al (2003 combined geophysical data and a conventional hydraulic test (a cross-hole test, not hydraulic tomography) as well as tracer tests to characterize the fracture-rock aquifer heterogeneity. Using the head responses induced by periodic slug tests, Guiltinan and Becker (2015) independently inverted the transmissivity and storativity in a sandstone bedrock containing a single, isolated subhorizontal fracture at the Altona Flat Rocks experimental site. They found that different oscillation periods lead to different estimates and periodic slug tests may be useful to establishing local scale spatial variability in hydraulic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be performed at multiple frequencies in order to assess impacts of heterogeneity or check for "frequency dependence" in aquifer parameters. While hardware for performing oscillatory pumping tests is more complex than the hardware needed for simple constant rate pumping tests, computer-controlled pumping systems using oscillating slugs (Guiltinan and Becker 2015) or pneumatic systems (the Pneusinehttp://hydroresolutions.com/hr_press/wp-content/uploads/2013/02/PneuSine-Test-HydroResolutions-LLC.pdf) are beginning to be "packaged" as tools for aquifer characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present concrete examples of this effect, using the 2-D solution. To demonstrate the issue, we utilize the same analysis approach applied by Rasmussen et al (2003), and later by Guiltinan and Becker (2015). As a review, the approach consists of the following steps which are used to estimate aquifer transmissivity T Kl  , storativity s S S l  , and diffusivity / D T S  :…”
Section: Processing With An Analytical (Homogeneous) Modelmentioning
confidence: 99%
See 2 more Smart Citations